Central Clearing and Risk Transformation - Rama Cont (Norges Bank, 2017)
The clearing of over-the-counter transactions through central counterparties (CCPs), one of the pillars of financial reform following the crisis of 2007-2008, has promoted CCPs as key elements of the new global financial architecture. It is important to examine how these reforms have affected risks in the financial system and whether central clearing has attained the initial objective of the reform, which is to enhance financial stability and reduce systemic risk. We show that, rather than eliminating counterparty risk, central clearing transforms it into liquidity risk: margin calls transform accounting losses into realised losses which affect the liquidity buffers of clearing members. Accordingly, initial margin and default fund calculations should account for this liquidity risk in a realistic manner, especially for large positions. While recent discussions have centred on the solvency of CCPs, their capital and 'skin-in-the-game' and capital requirements for CCP exposures of banks, we argue that these issues are secondary and that the main focus of risk management and financial stability analysis should be on the liquidity of clearing members and the liquidity resources of CCPs. Clearing members should assess their exposure to CCPs in terms of liquidity, rather than counterparty risk. Stress tests involving CCPs should focus on liquidity stress testing and adequacy of liquidity resources.
hdl:11250/2495593
Keywords: 330; CCP; OTC derivatives; central clearing; central counterparty; systemic risk; liquidity risk; counterparty risk; default fund; collateral requirement; regulation; stress testing